Hepatocellular carcinoma in thalassemia: A critical review - Mancuso, Andrea (Baishideng Publishing Group Co., Limited, 2010)
Due to blood transfusions, thalassemics are often infected with either hepatitis C virus (HCV) or hepatitis B virus and often have hemochromatosis. Hepatocellular carcinoma (HCC) has emerged in thalassemics only recently as a result of the improvement in thalassemia outcomes. In fact, a prospective study estimated an HCC incidence in β-thalassemia of about 2%. Although data are scanty, HCC screening in thalassemics with risk factors for HCC should be carried out. HCV treatments have some efficacy in HCV infected thalassemics despite partial contraindication to ribavirin and iron overload. However, there are no data on how HCV treatment translates into HCC prevention. Preliminary data suggest that HCC treatment in thalassemics should generally have the same outcomes as in non-thalassemics. Although coexistence of severe comorbidities makes liver transplantation challenging, this therapeutic possibility should not be precluded for well selected HCC β-thalassemia patients. In fact, 2 transfusion dependent adult HCC β-thalassemia patients have recently undergone successful liver transplantation with a good outcome. In conclusion, HCC seems to be a developing issue in thalassemia and HCC screening should be carried out. HCC treatment, including liver transplantation, can be performed in selected patients. A multidisciplinary effort is needed for management.